The COVID-19 Pandemic Through the Lens of a Medical Student in India - Surobhi Chatterjee (International Journal of Medical Students, 2020)
Online education in the pandemic era is a necessity for some and a substitute for others. Like any other form of communication, online education too has its fair share of constraints. Though, it has tried to address the lag of access during the time of pandemic but its universal access is still a matter of deep concern. As the pandemic progresses, so will our dependence on online education which needs to be tailored for students, educators and institutions.